Graphene Materials for Miniaturized Energy Harvest and Storage Devices. Issue 1 (13th January 2022) - Li, Xiangyang; Wang, Ying; Zhao, Yang; Zhang, Jing; Qu, Liangti
Abstract : Graphene Materials With a unique two‐dimensional structure, graphene material possesses numerous fascinating physical and chemical properties which endow it as promising candidate component or building block to boost such miniature devices system with superior performance and multifunctionality, including but not limited to active material, flexible substrate and electrically conductive additive. In article number 2100124, Yang Zhao, Liangti Qu, and co‐workers summarize the recent advances of graphene‐based materials for miniature energy harvesting and storage devices, including solar cells, mechanical energy harvesters, moisture and liquid flow generators, batteries and electrochemical capacitors, and their integrated devices. This review also discusses the challenges and future directions of grapheme materials in micro‐devices.